Clinical Profile and Outcome of Necrotizing Fasciitis - Pathak, Anand; Khadka, D. B.; Gautam, Subodh; Sharma, Anup; Bahl, Dig Vijay (Journal of Nepalgunj Medical College, 2017)
Background: Necrotizing fasciitis is soft tissue infection which spreads through the facial planes. It is a surgical emergency with its rapid onset and varied occult characteristic can cause diagnostic delays resulting in high mortality and morbidity. Objectives: To study the clinical profile and evaluate the determinants of outcome in patients with necrotizing fasciitis. Methods: A descriptive study of patients admitted and operated in the surgical units of Nepalgunj Medical College and Teaching Hospital Kohalpur with a diagnosis of necrotizing fasciitis from January 2013 to December 2015. Results: Total of 45 patients were included in the study. There were 27(60%) male and 18(40%) female, male to female ratio being 1.5: 1. The patient's age ranged from 2 to 76 years with mean age being 48.04±19.62 years. 38(84.44%) patients had no predisposing factor however trauma was the triggering factor in 4(8.89%) cases followed by surgery and insect bite. Diabetes mellitus 26(57.78%) and alcohol dependence 5(11.11%) cases were the most common co morbid condition associated with the disease. The lower limb 28(62.22%) was the most common site followed by upper limb, scrotum, perineum, trunk and abdomen. The growth was polymicrobial in 24(53.33%), mono microbial in 16(35.56%) and sterile in 5(11.11) cases . Staphylococcus aureus was predominant in 24(53.33%) cases followed by Streptococcus, E coli, Klebsiella, Enterococcus. The main procedure was debridement with secondary suturing 23(51.11%) and debridement with grafting in 18(40%) patient. Amputation was done in 2(4.44%) and secondary wound healing was observed in 2(4.44%) patients. 39(86.67%) cases improved with the above management while mortality was observed in 3(6.67%). 3(6.67%) cases left against medical advice so outcome was unknown Conclusion: On the basis of our study we concluded that high index of suspicion and awareness of the clinical presentation is required to diagnose this condition early. Diabetes mellitus is the most common co-morbid condition associated with necrotizing fasciitis. The presence of multiple co morbid conditions and delayed presentation reduces the survival rate. Early diagnosis and debridement, broad spectrum antibiotics with organ supportive intensive care will improve morbidity and mortality. JNGMC Vol. 14 No. 1 July 2016